Question 3: Factorize ( x + y) 2 -14z( x + y) + 49z 2

Question 3: Factorize   (x+y)^{2}-14z(x+y)+ 49z^{2}

Factorizing an expression —

Solution:

 

 

Given expression is

 (x+y)^{2}-14z(x+y)+ 49z^{2}

We convert this expression into  (a)^{2}-2(a)(b)+ (b)^{2}= (a-b)^{2} form!

= (x+y)^{2}-2(x+y)(7z)+ (7z)^{2}

= [(x+y)-(7z)]^{2}

== [x+y-7z]^{2}

 

This so because here as per formula;

x+y = a

and

z=b

and

 [(x+y)-(7z)]=a-b

 

 


					
					
Insert math as
Block
Inline
Additional settings
Formula color
Text color
#333333
Type math using LaTeX
Preview
\({}\)
Nothing to preview
Insert
Share